Alfacalcidol Increases the Therapeutic Efficacy of Ibandronate on Bone Mineral Density in Japanese Women with Primary Osteoporosis - Uchiyama, Shigeharu; Suzuki, Takako; Ikegami, Shota; Kamimura, Mikio; Kato, Hiroyuki; Nakamura, Yukio (The Tohoku Journal of Experimental Medicine, 2017)
Bisphosphonates (BPs) increase bone mineral density (BMD) through the inhibition of osteoclast activity. Among BPs, ibandronate (IBN) is a strong inhibitor of bone resorption. However, the effects of a vitamin D analogue, alfacalcidol (ALF), on IBN treatment for osteoporosis is unknown. Fifty-three treatment-naïve post-menopausal women with primary osteoporosis were recruited and divided into IBN-treatment group (IBN group) and IBN with ALF group (IBN/ALF group). IBN (1.0 mg) was intravenously injected once a month, with or without oral ALF (1.0 μg/day). Ultimately, 19 subjects in IBN group and 26 in IBN/ALF group were analyzed. Bone turnover markers were examined at 4, 6, 12, and 18 months, and BMD was measured at 6, 12, and 18 months. Compared with pre-treatment, bone turnover markers significantly decreased in both groups after 4 months. The levels of serum N-terminal propeptide of type-1 procollagen and tartrate-resistant acid phosphatase-5b, and urinary N-terminal telopeptide of type-I collagen were significantly lower in IBN/ALF group than those in IBN group at 12 months. Lumbar 1-4 (L)-BMD significantly increased from 6 months in IBN/ALF group and at 18 months in IBN group. L-BMD was significantly higher in IBN/ALF group (6.6% increase) than in IBN group (3.4%) at 18 months. Total hip (H)-BMD significantly increased from 6 months in IBN/ALF group and tended to improve in IBN group. H-BMD was significantly higher in IBN/ALF group (4.8%) than in IBN group (3.2%) at 18 months. In conclusion, treatment with ALF in combination with IBN improves BMD in post-menopausal women with osteoporosis.